High‐Speed OLEDs and Area‐Emitting Light‐Emitting Transistors from a Tetracyclic Lactim Semiconducting Polymer. Issue 21 (15th August 2018) - Ahmad, Viqar; Shukla, Atul; Sobus, Jan; Sharma, Anirudh; Gedefaw, Desta; Andersson, Gunther G.; Andersson, Mats R.; Lo, Shih‐Chun; Namdas, Ebinazar B.
Abstract: Development of a new class of luminescent materials that show high‐speed response, high charge carrier mobility, and high brightness is desirable toward realization of next generation of devices, such as electrically pumped organic lasers, visible light communication instruments, and organic light‐emitting transistors. In this paper, high‐speed organic light‐emitting diodes (OLEDs) and high‐performance hybrid light‐emitting transistors from a new type of solution processable luminescent material, poly[thiophene‐2, 5‐diyl‐alt‐5, 10‐bis((2‐hexyldecyl)oxy)dithieno[3, 2‐c:3′, 2′‐h][1, 5]naphthyridine‐2, 7‐diyl] (PTNT), are reported. The OLEDs based on PTNT polymer exhibit a peak brightness of 8 × 10 5 cd m −2 and 40 MHz modulation frequency under 10 ns pulse operation. This modulation frequency is significantly higher than that of commercially available LEDs, used for visible light communication. Additionally, solution‐processed area‐emitting hybrid light‐emitting transistors with an external quantum yield of 0.25% at brightness of 250 cd m −2 are demonstrated. Finally, the paper provides device physics and optoelectronic properties of PTNT polymer using ultraviolet photon spectroscopy, inversed photoelectron spectroscopy, and photophysical measurements. Abstract : Organic light‐emitting diodes (OLEDs) can be employed in visible light communications and lasers. In this work, high‐speed OLEDs and area‐emitting light‐emitting transistors using a tetracyclic lactim polymer are reported. This work provides device physics and OLED comparison with other polymers along with ultraviolet photon spectroscopy, inversed photoelectron spectroscopy, and photophysical measurements of the polymer.